Analisis Faktor-Faktor yang Mempengaruhi Perilaku Konsumen Dalam Membeli Polis Asuransi Jiwasraya - Siti Asiah; Nuri Aslami (Transformasi Manageria: Journal of Islamic Education Management, 2022)
Abstract This investigation intends to decide the elements that impact buyer conduct in purchasing extra security approaches. These variables are social, individual, mental, item, premium and advancement factors. This investigation was directed at PT. (Persero) Asuransi Jiwasraya Pekanbaru City, where the populace is all purchasers of disaster protection strategies in 2013 upwards of 500 individuals and upwards of 100 individuals were taken as tests. Gathering information utilizing a survey/poll and the testing strategy is a purposive examining method. The information examination utilized was enlightening, to be specific information investigation by gathering information and afterward explaining dependent on gatherings and classes, then, at that point, classified and portrayed by hypotheses pertinent to this exploration. The consequences of the review show that social, individual, mental, item and charge factors will be factors that extraordinarily impact the acquisition of disaster protection approaches dependent on respondents' reactions. Other than that, of these elements, the most predominant or the most compelling on buyer buying choices in purchasing extra security approaches are item factors comprising of convictions/perspectives and advantages/benefits. Keywords: Insurance Consumer Behavior and Policy Purchase